Recent Publications (Quarterly Journal of Economics, 1948)
Recent Publications The Quarterly Journal of Economics, Volume 62, Issue 4, August 1948, Pages 639–640, https://doi.org/10.1093/qje/62.4.639 Published: 01 August 1948